PENGARUH BRAND AMBASSADOR DAN EVENT SPONSORSHIP TERHADAP PURCHASE INTENTION DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING ( Studi Kasus Produk Smartphone Vivo pada Mahasiswa Universitas Sultan Ageng Tirtayasa ) - Ernie Larasari; Lutfi Lutfi; Liza Mumtazah (Sains: Jurnal Manajemen dan Bisnis, 2018)
This study aims to determine influence brand ambassador and event sponsorship on purchase intention (Y) through brand image(Z) as intervening variable on Vivo smartphone product. The method used in this research is quantitative research with descriptive approach. The population in this study is all the students of the University of Sultan Ageng Tirtayasa who is not a user of Vivo smartphones. The samples were 100 students of Sultan Ageng Tirtayasa University using accidental sampling method. Technique of the analysis used in this research is Structural Equation Modelling (SEM) with analysis tool by SmartPLS 3.0 student version. The result of this study show that : (1) Brand ambassador has positive and no significant effect on purchase intention, (2) Event sponsorship has negative and no significant effect on purchase intention, (3) Brand ambassador has positive and significant effect on brand image. (4) Event sponsorship has positive and significant effect on brand image. (5) Brand image has positive and significant effect on purchase intention (6) Brand image can mediate the relationship between brand ambassador with purchase intention (7) Brand image can mediate the relationship between event sponsorship with purchase intention.